The Proteasome-Ubiquitin System Is Required for Efficient Killing of Intracellular Streptococcus pneumoniae by Brain Endothelial Cells - Federico Iovino (American Society for Microbiology, 2014)
ABSTRACT Streptococcus pneumoniae (pneumococcus) is a Gram-positive bacterium that causes serious invasive diseases, such as pneumonia, bacteremia, and meningitis, with high morbidity and mortality throughout the world. Before causing invasive disease, S. pneumoniae encounters cellular barriers, which are often composed of endothelial cells, like the alveolar-capillary barrier and the blood-brain barrier. S. pneumoniae adheres to endothelial cells and may invade them, which requires an efficient host response to the intracellular bacteria. The precise intracellular fate of S. pneumoniae during infection still remains a subject of debate. The proteasome-ubiquitin system is largely responsible for the degradation of misfolded, damaged, or no-longer-useful proteins. Recently, the role of the proteasome-ubiquitin system in the clearing of invading bacteria and viruses has been more closely studied. In this study, we show that inhibition of the proteasome-ubiquitin system leads to a marked increase in S. pneumoniae survival inside host cells. Immunofluorescence analysis showed that intracellular pneumococci colocalized with proteasome and ubiquitin in human endothelial cells in vitro. Confocal imaging analysis demonstrated that in the brains of mice intravenously infected with S. pneumoniae, the bacteria were inside endothelial cells, where they colocalized with proteasome and ubiquitin signals. In conclusion, our data indicate that a fully functional proteasome-ubiquitin system in endothelial cells is crucial for efficient killing of intracellular S. pneumoniae. IMPORTANCE Bacterial meningitis is a serious invasive disease with high morbidity and mortality. How bacteria traverse the blood-brain barrier in vivo and what mechanisms are employed by the host to prevent invasion are still unclear. Our data show that inhibition of the proteasome-ubiquitin system in vitro leads to a significant increase in S. pneumoniae survival inside brain endothelial cells. Confocal imaging analysis of brain tissue from mice intravenously infected with pneumococci demonstrated that the bacteria are inside brain microvascular endothelial cells, where they associate with the proteasome and ubiquitin. This is, as far as we know, the first report that demonstrates that Streptococcus pneumoniae invades endothelial cells of the blood-brain barrier in vivo. The host requires the proteasome-ubiquitin system for an efficient decimation of intracellular S. pneumoniae.